2016
DOI: 10.3390/ijerph13070643
|View full text |Cite
|
Sign up to set email alerts
|

Household Air Pollution Exposure and Influence of Lifestyle on Respiratory Health and Lung Function in Belizean Adults and Children: A Field Study

Abstract: Household air pollution (HAP) contributes to the global burden of disease. Our primary purpose was to determine whether HAP exposure was associated with reduced lung function and respiratory and non-respiratory symptoms in Belizean adults and children. Our secondary purpose was to investigate whether lifestyle (physical activity (PA) and fruit and vegetable consumption (FV)) is associated with reported symptoms. Belizean adults (n = 67, 19 Male) and children (n = 23, 6 Male) from San Ignacio Belize and surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Clark et al () reported increased levels of PM 2.5 with increased FEV 1 values among Honduran women. Kurti et al () found no association between lung function of adults with HAP exposure, but reported an association for children. These studies suggest that chronic exposure may have reduced the susceptibility of mothers (Clark et al, ; Regalado et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Clark et al () reported increased levels of PM 2.5 with increased FEV 1 values among Honduran women. Kurti et al () found no association between lung function of adults with HAP exposure, but reported an association for children. These studies suggest that chronic exposure may have reduced the susceptibility of mothers (Clark et al, ; Regalado et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…4,48,50,51 Women using SBF as primary fuel showed a decline of 7.62% in FEV 1 /FVC ratio in comparison to clean fuel users. [52][53][54][55] Gupta and Kaul 56 also reported a considerable reduction in lung function values among the population dependent on SBF. Sana et al 16 summarized available studies on potential health risk associated with SBF uses and suggested to identify the chemical constituents of HAP for better understanding of biomass exposure and the onset as well as aggravation of respiratory diseases.…”
Section: Lung Function Assessmentmentioning
confidence: 94%
“…If two measurements varied by ≥ 10% of one another, a third measurement was taken. These assessments have previously been performed in our laboratory (Kurti et al, 2016(Kurti et al, , 2017. The assessment was conducted according to the American Thoracic Society guidelines for measuring eNO (Dweik et al, 2011).…”
Section: Experimental Designmentioning
confidence: 99%